ResNetVision: Harnessing Deep Learning for Early Skin Cancer Detection - S, Sheeba Rachel; S, Raahul K; S, Vignesh J; R, Ramya (2025 International Conference on Computing and Communication Technologies (ICCCT), 2025)
The skin is the largest organ of the human body. The skin is essential to regulating the body temperature and relaying sensations. Unfortunately, there is an increasing prevalence of skin-related diseases, even skin cancer which can be lethal, due to a host of factors like genetic influences, environmental polluters, and unhealthy diet. For effective complication remediation and life saving, these diseases must be dealt with in a timely fashion. Traditional diagnostic procedures normally take time and have errors, resulting in less than ideal results. This particular area of research deals with skin cancer and provides a new method for its early and accurate detection using modern computer technologies such as deep learning and [machine learning. The curation and the preprocessing of the big dataset which consists of images of skin lesions is accomplished through the use of the modern Convolutional Neural Network (CNN) methods.